Analysis of Pregnancy, Labor and Perinatal Outcomes of Women with Syphilis - A. N. Rymashevsky; A. E. Volkov; A. Р. Pavlova; E. D. Yudina (Медицинский вестник Юга России, 2011)
Purpose: To estimate the influence of infection with syphilis during pregnancy, birth and state of the newborn.Materials and Methods: surveyed 51 pregnant women with syphilis (study group). Comparison group consisted of 124 apparently healthy women with physiological pregnancy. In the groups evaluated parity, clinical and laboratory parameters of blood (blood count, hematocrit, leukocyte index of intoxication), during pregnancy, birth, state of newborn babies and their incidence.Results: The condition of pregnant women with siphyllis, significantly different from the state of apparently healthy women. Pregnancy in syphilis more severe with a high incidence of personal time complications. The combination of syphilis with other specific infectious disease worsens during pregnancy. Influence of syphilis during the birth itself and the frequency of obstetric complications among women in childbirth was not revealed. Women with syphilis were significantly more premature babies are born. Differences in the incidence of other perinatal diseases were found. The combination of syphilis with other specific infectious diseases greatly in creases the incidence of perinatal pathology in infants.Summary: Syphilis is one of the factors influencing the course of pregnancy and development of perinatal pathology in infants.